Conceptual system maps to guide research and management of multiple ecosystem services and disservices - Pablo García-Díaz; Yohana G. Jimenez; Carlos Molineri; María G. Quintana; Ezequiel Aráoz; Agustina Malizia; Oriana Osinaga Acosta; Priscila A. Powell; Cecilia Blundo; Sergio J. Ceballos; Ana D. Fuenzalida; M. de Lourdes Gultemirian; et al. (Perspectives in Ecology and Conservation)
Integrated assessments of multiple natural capital and ecosystem services and disservices (ESD) are needed to guide research and management in South America. Unfortunately, a poor understanding of the drivers of ESD and a scarcity of data undermine these efforts. Here, we combine expert knowledge and network analyses to create conceptual system maps to support the research and management of multiple ESD. Using the example of the Lules River watershed (northwestern Argentina), we integrated the biotic, abiotic, socio-economic, and policy drivers of five ESD selected due to their relevance to human well-being and biodiversity conservation in the area: (i) aboveground carbon stock; (ii) water quality; (iii) water quantity; (iv) dengue transmission; and (v) leishmaniasis transmission. Through facilitated activities, we encoded expert knowledge into networks representing drivers and causal interactions between those drivers. We recorded 43 drivers, of which 18 were identified as key drivers based on network metrics. The majority of key drivers were abiotic and socio-economic drivers (38.9% and 33.3% of 18, respectively), and we found potential information sources for all of these key drivers. Conceptual system maps provided significant benefits for guiding ESD research and ecosystem-based management. First, they formalised our current understanding of the system and provided a model that can be updated with new information. Second, they can be analysed through established network metrics to uncover relationships critical to effective system-level management and identify key drivers for data-gathering efforts. These maps offer a rapid and interdisciplinary tool to overcome existing barriers to integrated assessments in data-poor areas and are a powerful method to support system-based approaches to environmental management.